ANALISIS KESULITAN BELAJAR FISIKA MATERI ELASTISITAS DAN HUKUM HOOKE DALAM PENYELESAIAN SOAL – SOAL FISIKA - Hidayatulloh, Alpiana (Universitas Hamzanwadi, 2020)
This research was conducted in MA Yadaro, Moyot Village Class XI IPA. This study aims to analyze the difficulties faced by students when working on physics problems both in the form of pictorial questions and story problems. The material used in this study is about elasticity and hooke law. To see the difficulties faced by students an evaluation test in the form of a written test in the form of a picture problem and a story problem. Then the results of the evaluation were analyzed with a qualitative descriptive analysis, where students' answers were analyzed in two stages: the first stage: the analysis phase of the questions in all items and the second stage: the analysis of each item.